Long non-coding RNAs in the atherosclerotic plaque. (November 2017) - Arslan, Serdal; Berkan, Öcal; Lalem, Torkia; Özbilüm, Nil; Göksel, Sabahattin; Korkmaz, Özge; Çetin, Nilgün; Devaux, Yvan
Abstract: Background and aims: Genetic and environmental factors are important components of the development of atherosclerosis. Long non-coding RNA (lncRNAs) have emerged as regulators of multiple pathophysiological pathways in the cardiovascular system. Here, we investigated potential associations between lncRNAs and atherosclerosis. Methods: Tissue samples from atherosclerotic coronary artery plaques and non-atherosclerotic internal mammary artery were obtained from 20 patients during coronary artery bypass surgery. Expression levels of five lncRNAs known to be associated with coronary artery disease were measured using quantitative PCR. Results: Cyclin-dependent kinase inhibitor 2B antisense RNA 1 ( ANRIL ) and myocardial infarction–associated transcript ( MIAT ) were more expressed in the atherosclerotic arteries compared to the non-atherosclerotic arteries. Metastasis-associated lung adenocarcinoma transcript 1 ( MALAT1 ) was less expressed in the atherosclerotic plaques. Expression levels of potassium voltage-gated channel, KQT-like subfamily, member 1 opposite strand/antisense transcript 1 ( KCNQ1OT1 ) and hypoxia inducible factor 1A antisense RNA 2 ( aHIF ) were comparable between atherosclerotic and non-atherosclerotic arteries. In the atherosclerotic plaque, expression levels of MALAT1, MIAT, KCNQ1OT1 and aHIF were inversely correlated with age. Conclusions: We report significant associations between lncRNAs and atherosclerosis. These findings support a role for lncRNAs in coronary artery disease development. Highlights: To address the association of long-non coding RNAs (lncRNAs) with atherosclerosis. Arteries with or without atherosclerotic plaque were obtained from the same patient. Five lncRNAs associated with coronary artery disease were assessed. Three lncRNAs were modulated in the atherosclerotic tissue. Four lncRNAs were correlated with age, specifically in the atherosclerotic tissue.